Outcome of endovascular salvage of immature hemodialysis arteriovenous fistulas. Issue 4 (July 2019) - Kim, Yaeni; Chung, Byung Ha; Choi, Bum Soon; Park, Cheol Whee; Yang, Chul Woo; Kim, Yong-Soo
Purpose: To assess the causes of immature hemodialysis arteriovenous fistula and the outcome of endovascular salvage. Methods: The outcome of 207 endovascular salvage procedures in 139 patients after the first successful cannulation was analyzed retrospectively from January 2011 to December 2017 in the Catholic University of Korea, Seoul St. Mary's Hospital. Results: Of the 139 patients aged 62 ± 13 years, 45% were women, 59% had diabetes, and 71% were maintained on hemodialysis using central venous catheters. Mean interval between arteriovenous fistula creation and referral to angiography was 87 ± 63 days. While inflow stenosis (54.4%) was the most common cause of immature forearm fistulas (n = 76), both inflow (38.6%) and mixed stenosis (35.1%) were the main causes of immature upper arm fistulas (n = 63). Endovascular salvage procedures included percutaneous transluminal angioplasty (n = 174) and accessory vein obliteration (n = 30). The overall technical and clinical success rates were 97% and 93.4%, respectively. Mean interval between endovascular procedure and the first successful cannulation of the fistula was 28 ± 35 days. At 3, 6, and 12 months following the first successful cannulation, the primary patency rates were 81%, 69.5%, and 57.6%, respectively, and the secondary patency rates were 97.2%, 96%, and 94.8%, respectively. Mixed stenosis was the only determinant of secondary patency rate of immature arteriovenous fistula (hazard ratio = 6.334, confidence interval = 1.364–29.423, p  = 0.018), and patients with mixed stenosis had poorer access outcomes ( p  = 0.016). Conclusion: Immature arteriovenous fistulas can be successfully salvaged by aggressive and timely endovascular intervention. Mixed stenosis is associated with poor access outcomes.